THE CRIMINAL LIABILITY FOR ILLEGAL BANKING ACCESS WHICH HARMS STATE FINANCES - Manurung, Ridho Syahputra (UNISSULA, 2023)
The misuse of developments in information technology has in fact given rise to a new mode of theft crime, namely the development of theft by certain parties who use electronic means. The purpose of this research is to know and analyze the Scope of Cyber Crime by accessing electronic banking systems that harm the Bank's finances, Legal Protection for Banks That Suffer Losses Due to Actors Accessing the Bank's Electronic System, Criminal Liability for Cyber Crime Actors By Accessing Electronic Banking Systems That Harm State Finances. The research method used is library research (library study), in legal research the normative juridical approach method or library law. This crime is often perceived as a crime committed in the cyber area. The mode of operation of this crime continues to develop, along with technological developments. Crimes that arise as a result of the misuse of technological advances are cyber crimes by accessing electronic systems. Cyber Crimeas a crime that uses computer technology as the main component which is very detrimental and disturbing to society is a form of crime found in the mass media, namely all kinds of use of computer networks. Electronic Information and Transactions in the form of cellphones, laptops, internet. Because of this, Cyber Crime is often a reported modes of operation also vary, ranging from fraudulent sales of goods, embezzlement, fraud through stock investment, hijacking customers' ATMs and so on.